Pharmacodynamics of efavirenz 400 mg in treatment-naïve Chinese HIV-infected patients in a prospective cohort study - Xu, Ling (BMC Infect Dis, 2021)
BACKGROUND: The plasma concentration of patients treated with efavirenz (EFV) 600 mg was found to exceed the upper limit of the proposed therapeutic window in most Chinese HIV-infected individuals; thus, dosage reduction of EFV to 400 mg daily warranted consideration. This study aimed to assess the pharmacodynamics of EFV 400 mg for HIV-1-infected patients in China. METHOD: Twenty cART-naïve individuals were enrolled in this study. EFV 400 mg combined with tenofovir (TDF) and lamivudine (3TC) as an initial antiretroviral regimen was administered for 48 weeks. EFV concentration and T cell subsets as well as HIV RNA load were evaluated at baseline and at 4, 12, 24, and 48 weeks. Moreover, neuropsychiatric adverse effects were also assessed by the Hamilton depression (HAMD) scale and Pittsburgh sleep quality index (PSQI). RESULTS: Eighteen males and two females whose median age was 26 (interquartile range [IQR]: 23–32) years completed 48 weeks of follow-up. The median EFV concentrations were 1.88 (IQR: 1.54–2.42), 1.74 (IQR: 1.36–1.93), 1.93 (IQR: 1.66–2.22), and 1.85 (IQR: 1.54–2.14) mg/L at weeks 4, 12, 24, and 48, respectively. The viral load was 4.59 (IQR: 4.10–5.19) log(10) copies/mL at baseline, and it decreased by 4.6 (IQR: 3.98–5.18) log(10) copies/mL from baseline to week 48. Three of 20 (15%), 10 of 20 (50.0%), 17 of 20 (85%), and 18 of 19 (95%) participants had a plasma viral load less than 50 copies/mL at weeks 4, 12, 24, and 48, respectively. The median CD4 cell count was 330 (IQR: 237–410) cells/μL at baseline, and it increased to 473 (IQR: 344–574) cells/μL at 48 weeks. The HAMD score was 5 (IQR: 3–9.8) and 3 (IQR: 2.25–4) at baseline and 48 weeks, respectively. The PSQI score was 4 (IQR: 2–5.8) and 3 (IQR: 2–4) at baseline and 48 weeks, respectively. Dizziness was the most common event, occurring in 70% of patients within the first 2 weeks of treatment. CONCLUSION: Patients prescribed with EFV 400 mg-containing agents demonstrated favourable virological and immunological responses. And the plasma EFV concentration was within the recommended therapeutic range, with fewer adverse reactions than with EFV 600 mg. EFV 400 mg was effective and safe in Chinese HIV-infected patients. TRIAL REGISTRATION: NCT04596488; Registered 21 October, 2020; Retrospectively registered.